Xynocoris, new genus of Ochlerini from Central and South America (Hemiptera: Pentatomidae: Discocephalinae) - Garbelotto, Thereza De A.; Campos, Luiz A.; Grazia, Jocelia (Zootaxa, 2014)
Xynocoris Garbelotto & Campos gen. nov. is proposed for a monophyletic group recovered in the previous cladistic analysis of the Herrichella clade. The genus is proposed based in two synapomorphies: the presence of long, projected, and acute anteocular processes, and apices of posterolateral angles of pygophore tumid. Nine new species are described (X. crinitus Garbelotto & Campos sp. nov., X. recavus Garbelotto & Campos sp. nov., X. tuberculatus Garbelotto & Campos sp. nov., X. insularis Garbelotto & Campos sp. nov., X. egeri Garbelotto & Campos sp. nov., X. calosus Garbelotto & Campos sp. nov., X. meridionalis Garbelotto & Campos sp. nov., X. lucidus Garbelotto & Campos sp. nov. and X. cupreus Garbelotto & Campos sp. nov.) and one new combination is proposed for Alitocoris parvus (Distant).